Propagation of short radio waves - Kerr, Donald E. (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1987)
This book about short wave radio propagation is divided into eight chapters: elements of the problem; theory of propagation in a horizontally stratified atmosphere; meteorology of the refraction problem; experimental studies of refraction; reflections from the Earth's surface; radar targets and echoes; meteorological echoes; and atmospheric attenuation.